Effect of Cryogenic Treatment on Tungsten Welding Electrode - Renjith Nimal, R.J. Golden; Kohila, N. (International Journal of Psychosocial Rehabilitation, 2019)
Cryogenic treatment is the process of treating work pieces to cryogenic temperatures i.e. below -194 °C to remove residual stresses and improve wear resistance on steels and other materials. The process has a wide range of applications to industrial tooling for improvement, Some of the benefits of cryogenic treatment include longer part life, less failure due to cracking, improved thermal properties, better electrical properties including less electrical resistance, reduced coefficient of friction, less creep and walk, improved flatness, and easier machining. Cryogenic treatment has been widely acknowledged as a means of extending electrode life and low thermal shock and thus improving the life of electrode cycles. There are several theories concerning reasons for the effects of cryogenic treatment. One theory involves the more nearly complete transformation of retained austenite into martensite. Another theory is based on the strengthening of the material brought about by the precipitation of submicroscopic carbides as a result of the cryogenic treatment. Another theory is to relief of internal stresses and grain size reduction. Pure tungsten is used as electrodes for Resistance welding, when the electrodes are in direct contact with work piece, Grain coarsening are taken place in the tip area. This is called as Tip heating. The grain coarsening effect of electrode tip is delayed due to the cryogenic treatment of electrodes. This will improve the life of electrodes